Aeromonas species from raw squid balls a preliminary study of a potential food-borne pathogen and health hazard - Baldrias, Loinda R. (Journal of Environmental Science and Management, 1999)
The presence of Aeromonas spp., an emerging food-borne pathogen, was determined in 57 raw squid-ball samples bought from three different retail outlets in the vicinity of the University of the Philippines Los Banos (UPLB) campus over a period of four months. It was found that 10 (17.5 percent) of the 57 raw squid-ball samples were positive for the presence of Aeromonas spp. Seven (12.3 percent) isolates were identified as A. hydrophila and three (5.2 percent) as A. caviae. The recovery of Aeromonas spp. from the raw squid-balls sold by street-food vendors within the vicinity of the UPLB campus maybe a public health concern, the organism being a possible food-borne hazard. Hence, it is important that consumers ensure that squid-balls puchased are adequately thawed and properly cooked prior to consumption